Analysis and experimental investigation for collimator reflective mirror surface deformation adjustment - Chia-Yen Chan; Zhen-Ting You; Ting-Ming Huang; Yi-Cheng Chen; Fong-Zhi Chen (Terrestrial, Atmospheric and Oceanic Sciences, 2017)

(untitled)
Collimator design is essential for meeting the requirements of high-precision telescopes. The collimator diameter should be larger than that of the target for alignment. Special supporting structures are required to reduce the gravitational deformation and control the surface deformation induced by the mounting force when inspecting large-aperture primary mirrors (M1). A ZERODURÂŽ mirror 620 mm in diameter for a collimator was analyzed using the finite element method to obtain the deformation induced by the supporting structures and adjustment mechanism. Zernike polynomials were also adopted to fit the optical surface and separate corresponding aberrations. The computed and measured wavefront aberration configurations for the collimator M1 were obtained complementally. The wavefront aberrations were adjusted using fine adjustment screws using 3D optical path differences map of the mirror surface. Through studies using different boundary conditions and inner ring support positions, it is concluded that the optical performance was excellent under a strong enough supporter. The best adjustment position was attained and applied to the actual collimator M1 to prove the correctness of the simulation results.